2012
DOI: 10.1177/230949901202000211
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Using Cannulated Screws and Fibular Strut Grafts for Fresh Femoral Neck Fractures with Posterior Comminution

Abstract: Osteosynthesis and fibular grafting for freshly displaced femoral neck fractures with posterior comminution is an inexpensive and technically less demanding procedure for retaining a stable, painless, mobile, and functional hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
0
26
3
Order By: Relevance
“…Our study is comparable with Zahid et al, who reported a series of 37 patients treated with fixation using cannulated screws and fibular strut grafts for fresh femoral neck fractures with posterior comminution. 28 Harris hip score was good to excellent in 20 patients, fair in 7, and poor in 6 while in our study the Harris Hip Score of 30 patients in group A and 12 patients in group B had excellent results and 06 patients in group A and 24 patients in group B had good results. Our study is comparable with Goyal et al Who showed union in 15 patients with 24 months follow up with fibular grafting and MHS.…”
Section: Discussioncontrasting
confidence: 39%
“…Our study is comparable with Zahid et al, who reported a series of 37 patients treated with fixation using cannulated screws and fibular strut grafts for fresh femoral neck fractures with posterior comminution. 28 Harris hip score was good to excellent in 20 patients, fair in 7, and poor in 6 while in our study the Harris Hip Score of 30 patients in group A and 12 patients in group B had excellent results and 06 patients in group A and 24 patients in group B had good results. Our study is comparable with Goyal et al Who showed union in 15 patients with 24 months follow up with fibular grafting and MHS.…”
Section: Discussioncontrasting
confidence: 39%
“…Thus, adults with posterior comminution can benefit from primary fibular osteosynthesis even in fresh fracture neck of femur as reported in leterature. [18][19][20] Our result shows this simple procedure can be done at simple orthopedic facilities with image intensifier.…”
Section: Resultsmentioning
confidence: 88%
“…[7][8][9]13,23,29 Primary autologous fibular grafting along with cancellous screw fixation in fresh cases has been done and good results have been reported by two workers. 13,15 In this study we have used fibular autograft in all our patients. Since being young, they do not have the option of replacement of femoral head.…”
Section: Why a Graft?mentioning
confidence: 99%
“…C) vascularized fibular graft have been advocated along with or without internal fixation along with valgus osteotomy to treat neglected fractures and ununited femoral neck fractures to promote union. [5][6][7][8][9][10][11][12][13][14][15][16][17] Bone graft supplementation by using free fibular grafting was in past used in fifth decade but with less satisfying results. [18][19][20] In India it was revived in 1981 and first results were published in 1986.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation